Student’s knowledge of obesity at the Collegium Medicum of the Jan Kochanowski University in Kielce - Redziak, Kamil Grzegorz (Journal of Education, Health and Sport, 2020)
Introduction: Obesity is considered to be an epidemic of the XXI century. According to the World Health Organisation (WHO), the number of overweight people aged 18 and over in 2016 was 1.9 billion, 650 million of whom were obese. The causes of obesity are mainly due to erroneous eating habits and low levels of physical activity. Obesity is a disease, but it is also a factor causing many diseases, including chronic diseases that can lead to disability and premature death. Aim: The aim of the study was to assess the level of knowledge of students of the Faculty of Medicine and Health Sciences of Jan Kochanowski University in Kielce about the causes and effects of obesity. Material and methods: In this work, we used a self-assessment questionnaire to conduct the research. The survey was conducted among students of Collegium Medicum of Jan Kochanowski University in Kielce. The research group consisted of 111 students, including 98 students and 13 students. The respondents lived in both urban and rural areas. Results: The analysis of the collected data shows that the students have knowledge about obesity, know the causes, health effects and show that extensive preventive actions will contribute to reduce the incidence of obesity. Conclusions: Students have a high knowledge of obesity, correctly identifying the causes and methods of diagnosis of obesity. They also have sufficient knowledge of the impact of obesity on health.